John Singleton Mosby papers - Mosby, John Singleton, 1833-1916.
Chiefly correspondence, orders, commissions, reports, and circulars concerning the organization and activities of Mosby's Rangers (43rd Virginia Cavalry Battalion, C.S.A.). Documents the guerrilla warfare carried out by the battalion in Virginia. Contains remarks on public enthusiasm for the war in 1861, the treatment of prisoners of war, casualties, the death of Maj. John Pelham, and the capture of Gen. Edwin H. Stoughton. Correspondents include Jubal Anderson Early, Joseph E. Johnston, Robert E. Lee, Henry E. Peyton, Alexander Hamilton Stephens, Jeb Stuart, and Mosby's wife, Pauline.
Chiefly negative photostats.
Photostats produced from originals with permission of Mrs. Stuart Mosby Coleman.
Confederate army officer, lawyer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Early, Jubal Anderson, -- 1816-1894 -- Correspondence; Johnston, Joseph E. -- 1807-1891 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Mosby, Pauline -- Correspondence; Pelham, John, -- 1838-1863.; Peyton, H. E. -- Correspondence; Stephens, Alexander Hamilton, -- 1812-1883 -- Correspondence; Stoughton, Edwin H. -- 1838-1868.; Stuart, Jeb, -- 1833-1864 -- Correspondence; Confederate States of America. -- Army. -- Virginia Cavalry Battalion, 43rd.; Guerrilla warfare; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Casualties; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865 -- Public opinion; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Army officers, Confederate; Authors; Lawyers